N‐oxide‐Functionalized Bipyridines as Strong Electron‐Deficient Units to Construct High‐Performance n‐Type Conjugated Polymers - Mingwei Li; Wenhao Li; Junkang Zhou; Xiaowen Tian; Hongxiang Li; Zhen Jiang; Di Liu; Yunqi Liu; Yang Wang; Yongqiang Shi (Advanced Science, 2025)
Abstract Developing low‐cost unipolar n‐type organic thin‐film transistors (OTFTs) is necessary for logic circuits. To achieve this objective, the usage of new electron‐deficient building blocks with simple structure and easy synthetic route is desirable. Among all electron‐deficient building units, N‐oxide‐functionalized bipyridines can be prepared through a simple oxidized transformation of bipyridines. However, employing N‐oxide‐functionalized bipyridines as the building unit to construct efficient N‐type polymers has been overlooked. This gap strongly encourages us to design and synthesize two new N‐oxide building blocks, 5,5'‐dibromo‐[2,2'‐bipyridine] 1‐oxide (BPyO) and 5,5'‐dibromo‐[2,2'‐bipyridine] 1,1'‐dioxide (BPyDO), through the oxidation of sp2‐N in 2,2ʹ‐bipyridine. The single‐crystal X‐ray diffraction shows that BPyO and BPyDO possess planar structure with strong π‐stacking, which is beneficial for charge transport. Incorporation of these building blocks into acceptor–acceptor backbones leads to two new polymers, namely P(DPP‐BPyO) and P(DPP‐BPyDO). Both P(DPP‐BPyO) and P(DPP‐BPyDO) possess lower frontier molecular orbital energy levels than the non‐oxide polymer P(DPP‐BPy). Consequently, the transition from P(DPP‐BPy) (without oxide group) to P(DPP‐BPyO) (mono‐oxide group) and then to P(DPP‐BPyDO) (dioxide group) can decrease hole‐transport performance and gradually switch the transport nature from p‐type to n‐type via ambipolar. These results prove that the introduction of sp2‐N oxide groups in building units would be a promising strategy to approach high‐performance n‐type polymers.